(2+3) amide cages by oxidation of (2+3) imine cages: revisiting molecular hosts for efficient nitrate binding [data] - Lauer, Jochen; Bhat, Avinash S.; Barwig, Chantal; Rominger, Frank; Mastalerz, Michael (Universität, 2022)
The pollution of groundwater with nitrate is a serious issue because nitrate can cause several diseases such as methemoglobinemia or cancer. Theref...